A review of the use of Mirtazapine in cancer patients - Zaini, Syahrir; Ng, CG; Sulaiman, AH; Huri, NZ; Shamsudin, SH (Malaysian Psychiatric Association, 2016)
Cancer patients often have concurrent physical and psychological symptoms. These problems may become barriers towards the healing process. Antidepressants seem to be beneficial for the purpose of palliative care in this type of patients. One of the useful medications is mirtazapine, which is known as noradrenergic and specific serotonergic antidepressant (NaSSA). This paper examines the use of mirtazapine in physical and psychological symptoms of cancer patients. Methods: Literature search was done on PubMed (from inception to January 2017) by matching the key terms: ‘noradrenergic and specific serotonergic antidepressants’ or ‘NaSSA’ ‘mirtazapine’ AND ‘cancer’ or ‘oncol*’ or ‘malignancy’ or ‘carcinoma’. Eligible papers were screened at the title and abstract level. Various types of study included in this review, according to certain criteria. Additional papers were also identified by screening of reference lists. Results: A total of twelve papers were reviewed and summarized. Positive findings obtained for the use of mirtazapine in cancer patients associated with various symptoms, including depression, anxiety, cachexia, nausea, hot flashes, and pruritus. Some rare side effects are reported, including constipation, myalgia sedation, dry mouth, stimulation of appetite and weight gain. Conclusion: Mirtazapine has the potential to be beneficial for cancer patients suffering from these physical and psychological symptoms. However, more research studies with sufficient power are warranted to validate the findings.